In vitro analysis of Nisin Z-loaded biodegradable wet-spun fibers: controlled release for the inhibition of Staphylococcus aureus - Homem, Natália Cândido (2021)
This work is financed by FEDER funds through COMPETE and by national funds through FCT via the projects POCI-01-0145-FEDER-028074 and UID/CTM/00264/2020. CSM also acknowledges FCT for PhD grant (2020.08547.BD).